Deletion of IL-4 Receptor Alpha on B Lymphocytes renders BALB/c Mice balance Th differentiation to Leishmania major Infection during the early stage of Infection - NATARAJAN, SATHEESH; BROMBACHER, FRANK (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
B-lymphocytes are considered to play a minimal role in host defense against Leishmania major. In BALB/c mice, susceptibility to infection with the intracellular parasite Leishmania major is driven largely by the development of T helper 2 (Th2) responses and the production of interleukin (IL-4 and IL-13), which share a common receptor subunit, the IL-4 receptor alpha chain (IL-4Ra). To investigate the relevance IL-4Ra mediated signalling in B Lymphocytes independently of non-B cells during the early stage in vivo infection, B-lymphocytes specific IL-4RÎ± deficient (MB-1-hCreIL4Ra-/LOX) BALB/c mice were generated by gene targeting and site-specific recombination using the cre/loxP system under control of the MB-1 locus. DNA functional characterization through RT-PCR showed a balanced IL-4RÎ± expression on B-lymphocytes in MB-1-hCre IL4Ra-/LOX mice. We conclude from these data that the balanced expression shows that the Th differentiation doesn't happen in the early stage of infection and considered this an important host protective factor during early infection of cutaneous leishmaniasis.